2015
DOI: 10.2147/ijn.s80795
|View full text |Cite
|
Sign up to set email alerts
|

Inducing cell cycle arrest and apoptosis by dimercaptosuccinic acid modified Fe3O4 magnetic nanoparticles combined with nontoxic concentration of bortezomib and gambogic acid in RPMI-8226 cells

Abstract: The purpose of this study was to determine the potential benefits of combination therapy using dimercaptosuccinic acid modified iron oxide (DMSA-Fe 3 O 4 ) magnetic nanoparticles (MNPs) combined with nontoxic concentration of bortezomib (BTZ) and gambogic acid (GA) on multiple myeloma (MM) RPMI-8226 cells and possible underlying mechanisms. The effects of BTZ-GA-loaded MNP-Fe 3 O 4 (BTZ-GA/MNPs) on cell proliferation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The later effects are probably caused by the ions released (ROS generation) by magnetic MNPs that lead to the ignition of oxidative stress responses into the cell and at the end to cytotoxicity. Moreover, although iron MNPs degraded in the cell, they can change the cellular iron pool, leading to aberrant expression of transferrin receptor, cyclins, and induction of apoptotic responses [ 35 37 ]. Regarding cytotoxicity, the choice of the cell line tested under MNPs treatment is of great importance, since it is demonstrated that MNPs toxicity is highly cell-type dependent [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The later effects are probably caused by the ions released (ROS generation) by magnetic MNPs that lead to the ignition of oxidative stress responses into the cell and at the end to cytotoxicity. Moreover, although iron MNPs degraded in the cell, they can change the cellular iron pool, leading to aberrant expression of transferrin receptor, cyclins, and induction of apoptotic responses [ 35 37 ]. Regarding cytotoxicity, the choice of the cell line tested under MNPs treatment is of great importance, since it is demonstrated that MNPs toxicity is highly cell-type dependent [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Iron oxide NPs can enter B-cell lymphoma and multiple myeloma cells through phagocytosis and electrostatic interaction inducing cells autophagy and death. This induction of cells autophagy can be further non-invasively tuned by an external magnetic field [ 64 ] or by the addition of a chemotherapeutic agent, like bortezomib with gambogic acid [ 65 ].…”
Section: Nanoparticle-based Therapymentioning
confidence: 99%
“…A major advantage of a coating of polycyclophenazene is that it would help to reduce the tendency of the magnetic nanoparticles to aggregate together. The potential of such nanoparticles is an active area of research (Zhang et al, 2015;Kamble and Kolckar, 2014). …”
Section: In Vivo Applicationsmentioning
confidence: 99%